Evaluasi Implementasi Penegakkan Hukum Terhadap Kasus Pencemaran Nama Baik Di Media Sosial - Romadhan, Moh. Lubsi Tuqo; Rosma Tamami, Nadzirotin; Khoirul Ummah, Maela; Tanjung, Afriansyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2026)
In the digital age, the rapid dissemination of information often exceeds legal boundaries, making defamation on social media a complex social issue. This study aims to evaluate the implementation of laws on defamation cases on social media, particularly the effectiveness of the Electronic Information and Transaction Law (EIT Law) and the challenges in its application. The method used is a normative juridical approach with analysis of legislation, court decisions, and related legal literature. The results of the study show that, although the ITE Law has a strong legal framework, its implementation is hampered by difficulties in proving cases, lengthy court proceedings, and low public awareness of the limits of expression in cyberspace. These findings highlight the need for improvements in the reporting system, enhanced law enforcement capabilities, and digital education. This research increases understanding of legal changes in the digital age that affect public policy and the protection of human rights.